2018
DOI: 10.2174/1381612823666170825124515
|View full text |Cite
|
Sign up to set email alerts
|

Nasal Delivery of Antioxidants by Cholesterol-incorporated Liposomes Extends the Neuroprotective Time Window in Cerebral Ischemia

Abstract: Antioxidants have the potential to prevent cerebral ischemia-reperfusion (IR)-associated secondary damage induced by reactive oxygen species (ROS); however, the short therapeutic time window of IR is a considerable obstacle. Nano-sized nasal delivery systems provide an effective means of delivering drugs through the BBB, but few such systems have been developed to extend the treatment time window in IR. In this work, a nanosized nasal delivery system for antioxidants was found to have the potential to extend t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Chitosan-coated C-PC liposomes also protected rat primary astrocytes from H 2 O 2 toxicity, while decreasing the expression of TNF-α and inducing the phosphacan and neurocan genes, both glia scar-associated proteoglycans [ 122 ]. Previously, it has been observed that these C-PC encapsulated liposomes protected the murine Neuro2A cell line from H 2 O 2 toxicity [ 123 ]. Endothelial cells are also crucially involved in ischemic stroke damage, as they regulate brain inflammation [ 124 ] and can be damaged by a burst of toxic oxygen and nitrogen species, contributing to blood-brain barrier breakdown, CBF dysregulation, and vascular tone alteration [ 125 ].…”
Section: Nutraceutical Intervention In Neuro-degenerative Diseases By...mentioning
confidence: 99%
See 1 more Smart Citation
“…Chitosan-coated C-PC liposomes also protected rat primary astrocytes from H 2 O 2 toxicity, while decreasing the expression of TNF-α and inducing the phosphacan and neurocan genes, both glia scar-associated proteoglycans [ 122 ]. Previously, it has been observed that these C-PC encapsulated liposomes protected the murine Neuro2A cell line from H 2 O 2 toxicity [ 123 ]. Endothelial cells are also crucially involved in ischemic stroke damage, as they regulate brain inflammation [ 124 ] and can be damaged by a burst of toxic oxygen and nitrogen species, contributing to blood-brain barrier breakdown, CBF dysregulation, and vascular tone alteration [ 125 ].…”
Section: Nutraceutical Intervention In Neuro-degenerative Diseases By...mentioning
confidence: 99%
“…C-PC (134 µg/kg) administered intranasally to ischemic rats, showed an effective effect on the infarct volume decrease when applied for up to 9 h post-stroke [ 120 ]. Encapsulated C-PC in liposomes with 20% cholesterol also produced a dramatic reduction in the cerebral injury of rats when applied intranasally at 1 mg/mL (around 111.2 µg/kg considering a 300 g rat) 6 h after the ischemic event, decreasing the infarct volume to 23.2% in relation to the vehicle-treated group, even more than the protection seen in injured animals receiving non-encapsulated intranasal C-PC (68.97%) [ 123 ]. As chitosan material has been suggested to be a preferred system for delivery to the olfactory bulb (as opposed to the nasopharynx) through nasal mucin adhesion [ 128 ], a follow-up study tested the ability of cholesterol C-PC liposomes coated with chitosan for improving the neuroprotective action of the encapsulated biliprotein in IS.…”
Section: Nutraceutical Intervention In Neuro-degenerative Diseases By...mentioning
confidence: 99%
“…Excitingly, the therapy for neurological diseases utilizing C-PC and BNDD has been reported with promising results. Min et al have found that C-PC-based liposomes with 20% cholesterol administrated via the nose-to-brain system showed extended neuroprotective effects in animal models of cerebral ischemia ( Min et al, 2017 ). Additionally, Chung et al designed chitosan-coated C-PC liposome (C-PC liposome) and verified that nasal administration of C-PC liposome resulted in smaller infarct size and improved behavioral test outcomes in rat Middle Cerebral Artery Occlusion (MCAO) models in comparison to free C-PC ( Chung et al, 2018 ).…”
Section: Natural Products For the Treatment Of Crcimentioning
confidence: 99%